Exploring the perspectives of outpatient rehabilitation clinicians on the challenges with monitoring patient health, function and activity in the community. Issue 12 (5th June 2022) - Singh, Hardeep; Musselman, Kristin; Colella, Tracey J. F.; McGilton, Katherine S.; Iaboni, Andrea; Bayley, Mark; Zariffa, José
Abstract: Purpose: Rehabilitation clinicians need information about patient activities in the home/community to inform care. Despite active efforts to develop technologies that can meet this need, clinicians' perspectives regarding how information is collected and used in outpatient rehabilitation have not been comprehensively described. Therefore, we aimed to describe: (1) what data pertaining to a patient's health, function and activity in their home/community are currently collected in outpatient rehabilitation, (2) how these data can impact clinical decisions, and (3) what challenges clinicians encounter when they manage the care of outpatients based on this information. Materials and methods: Eight clinicians working in outpatient rehabilitation programs completed qualitative interviews that were analyzed using an inductive thematic analysis. Results: Four themes were identified: "Nature of data about a patient's health, function and activity in the home/community and how it is collected by clinicians, " "Value of data from the home/community, " "Perceived drawbacks of current data collection methods, " and "Improving data collection to understand patient trajectory." Conclusions: Clinicians described the importance of understanding patient activities in the home/community, but perspectives varied regarding the suitability of current methods. These perceptions may inform the design of solutions to bridge the gap between the clinic and the community in outpatient rehabilitation. Implications for rehabilitation: Clinical decision-making in outpatient rehabilitation is guided by verbal and written reports about a patient's health and function in the community and adherence to treatment plans. Differing perceptions on the suitability of current data collection methods indicate that the development of new solutions, such as rehabilitation technologies, needs to carefully consider clinician workflows and what data are perceived as meaningful. Potentially impactful directions for new solutions include providing well validated data on adherence, movement quality, or longitudinal progression, presented in formats that match clinical decision criteria.